ДО 180-РІЧЧЯ НАЦІОНАЛЬНОГО МЕДИЧНОГО УНІВЕРСИТЕТУ ІМЕНІ О.О. БОГОМОЛЬЦЯ - Волосовець, О.П.; Науменко, О.М.; Кривопустов, С.П.; Кузьменко, А.Я.; Дзюба, О.Л.; Логінова, І.О. (Українські медичні вісті, 2023)
ДО 180-РІЧЧЯ НАЦІОНАЛЬНОГО МЕДИЧНОГО УНІВЕРСИТЕТУ ІМЕНІ О.О. БОГОМОЛЬЦЯ